Always separate, always connected : independence and interdependence in cultural contexts of development - Raeff, Catherine, 1964- (Lawrence Erlbaum, 2006)
Presents conceptualization which holds that independence and interdependence are multifaceted and inseparable dimensions of human functioning that may be defined and enacted differently in different cultures. This book's focus is to delineate how independence and interdependence issues are related during development in culturally distinct ways.